Glossary of plants, animals and expressions (2014)
This glossary contains the biological identifications of plants and animals, and the definitions of terms and expressions in Witoto or local Spanish, that are mentioned in the texts “Do you want to know who Anastasia Candre is? Dear reader, here I am”; “Eiño jɨɨra: healing spell of the Mother”; and “Kaɨmakɨ guiye fɨnuafue: the preparation of the food of our people”, by Anastasia Candre, contained in this portfolio.